The Implementation Of Demonstration Strategy Using Modeling Videos To Improve Confidence And Practices In Presentation - Anggraeni, Dewi (LPPM Universitas Mercu Buana Yogyakarta, 2016)
AbstractThe objectives of this study were to explain the problems faced by engineering students of Semarang State Polytechnic in their presentation skills, to describe the implementation of demonstration strategy using modeling videos in improving the students’ self-confidence and practice in their presentation and the improvement when the strategy was applied. The research design of this study was classroom action research. The subjects were 20 engineering students from Telecommunication Study Program of Semarang State Polytechnic. The study was conducted by doing observation, giving pre test and posttest and questionnaire. The actions were conducted in three cycles. The findings showed that the implementation of demonstration strategy using modeling videos was able to improve the engineering students’ self-confidence and practice in their presentation skills. First, the students were actively involved in the teaching learning process. It could be seen from the result of observation sheet done by the researcher. There was an improvement of 3.3 points. Second, the posttest result showed significant progress from the pre test score, which was 69.8 into 84.95.